THE FUTURE OF FILIPINO CULTURE IN THE FACE OF CULTURE INDUSTRY - Eugenio, Paula Nicole Cuaresma (PEOPLE: International Journal of Social Sciences, 2016)
This paper aims to look into the future of Filipino culture in the face of culture industry through the investigation and critique of the popular literature today. The researcher tries to contextualize the fetishism of music in Adorno’s The Culture Industry and the role of the mass media in the proliferation of the prevalent type of reading materials that they call “literature” but does not qualify to be called as such. This paper will be divided into four parts: introduction of culture industry and the role of mass media, the fetish character of music, the fetish character of literature, and conclusion.